KLENIK MASYARAKAT PEDALAMAN: ANALISIS BUDAYA DALAM TIGA CERPEN KALIMANTAN TIMUR - Aquari Mustikawati (Kantor Bahasa Kalimantan Timur, 2017)
Three stories in East Kalimantan revealed ‘klenik’ or black magic in society in two different eras of 1970 and 2000 . This research tried to show some kinds of magical practices and cultural form to each magical practices . It applied qualitative approach and descriptive method with religion system in cultural theory . The magical practices and cultural forms in these short stories indicated that there were people in the past and present committed hidden magical practices for their wicked intention .